2003
DOI: 10.1063/1.1613932
|View full text |Cite
|
Sign up to set email alerts
|

Threshold ion-pair production spectroscopy of HCl/DCl: Born–Oppenheimer breakdown in HCl and HCl+ and dynamics of photoion-pair formation

Abstract: Accurate ab initio determination of the adiabatic potential energy function and the Born-Oppenheimer breakdown corrections for the electronic ground state of LiH isotopologues Threshold ion-pair production spectroscopy ͑TIPPS͒ has been applied to two isotopomers, HCl and DCl. From the high-resolution TIPP spectra the ion-pair thresholds of the two molecules have been precisely measured. Combined with the known ionization energy of H͑D͒ and the electron affinity of Cl, the difference between their bond dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
5
13
1
Order By: Relevance
“…It should be noted that in most experiments the ionization field F 2 is pulsed (PFI), thus transforming Rydberg states that are excited field-free into above-saddle point Stark states; it is then important whether evolution from low to high fields through crossings between the Stark manifolds, which are actually avoided crossings in all systems but the hydrogen atom, is diabatic or adiabatic. In the present experiment however, different from earlier TIPPS experiments [10,12,15,50], excitation occurs while the discrimination field F 1 is already present. Therefore all Stark states that may be involved in above-saddle point population loss are at the excitation energy, a situation that resembles adiabatic evolution in PFI.…”
Section: A Fit Function For the Tipps Spectracontrasting
confidence: 95%
“…It should be noted that in most experiments the ionization field F 2 is pulsed (PFI), thus transforming Rydberg states that are excited field-free into above-saddle point Stark states; it is then important whether evolution from low to high fields through crossings between the Stark manifolds, which are actually avoided crossings in all systems but the hydrogen atom, is diabatic or adiabatic. In the present experiment however, different from earlier TIPPS experiments [10,12,15,50], excitation occurs while the discrimination field F 1 is already present. Therefore all Stark states that may be involved in above-saddle point population loss are at the excitation energy, a situation that resembles adiabatic evolution in PFI.…”
Section: A Fit Function For the Tipps Spectracontrasting
confidence: 95%
“…͑4͔͒ was first found by Yencha et al 23 in one-photon processes using synchrotron radiation in the energy range 14.4-16.4 eV. Hepburn and co-workers 3,24 found similar results using threshold ion-pair production spectroscopy near 14.4 eV photon energy. The analysis of the results showed that the ion-pair is formed by the predissociation of Rydberg states with an A 2 ⌺ + ion core and nl electrons ͑n=4-6͒ by the diabatic curve of the V 1 ⌺ + ion-pair state.…”
Section: ͑1͒mentioning
confidence: 66%
“…The excited states and the dynamics involved in the photodissociation and photoionization of the HCl molecule and the corresponding ion HCl + have been the subject of a large number of spectroscopic and theoretical investigations. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Studies investigating the resonance enhanced multiphoton ionization ͑REMPI͒ [10][11][12][13][14][15][16][17][18][19][20] have revealed fascinating dynamics involving highly excited Rydberg states above the ionization limit. Particularly, the photodissociation and autoionization as well as the subsequent photodissociation of the highly vibrationally excited molecular ion HCl + following the twophoton excitation to the B 1 ⌺ + state have been of special interest.…”
Section: Introductionmentioning
confidence: 99%
“…In case of I 2 , vibrational levels as high as v > 600 have been observed by means of resonance enhanced multiphoton ionization . In recent years, high-resolution spectroscopic studies on ion-pair states have been performed to determine precise ion-pair dissociation limits and bond dissociation energies for neutral products. , In these studies, a pulsed DC field was used after a certain delay relative to the excitation laser pulse to induce the threshold ion-pair dissociation. Hepburn and co-workers termed the method as threshold ion-pair production spectroscopy (TIPPS) , and successfully applied it to a number of molecular systems, whereas Donovan and co-workers called it zero ion kinetic energy (ZIKE) 5 spectroscopy because of the exact analogy to the previously known zero electron kinetic energy (ZEKE) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%